Visual acuity testing in preschool children: Freiburg acuity test (FrACT) vs LEA symbols test - Farassat, Navid; Jehle, Vanessa; Heinrich, Sven; Lagrèze, Wolf; Bach, Michael (Acta ophthalmologica (Oxford, England), 2024)
Aims/Purpose: Cross‐sectional study to compare testability and performance of the Freiburg Visual Acuity Test (FrACT) and LEA Symbols Test (LEA) and to determine test–retest variability of visual acuities (VAs) achieved with the FrACT in preschool children. Methods: Monocular VA of both eyes was measured in 136 preschool children (268 eyes) aged 3.0 to 6.8 years – once with the LEA and twice with a 4‐orientation Landolt C version of the FrACT. The monocular FrACT runs were preceded by a binocular run for explanatory purposes. The test order alternated between subjects. Optotypes were presented either on a computer monitor (FrACT) or on cards (Lighthouse Single Symbol Book; LEA) at a distance of 3 m. Results: The overall testability of children was 70.1% for FrACT (188 of 268 eyes) and 90.3% for LEA (242 of 268 eyes). Testability depended markedly on age, with children aged <4 years at 23.0% (FrACT), 73.0% (LEA); ≥ 4 years: 88.1% (FrACT), 96.9% (LEA). The mean VA difference between FrACT and LEA was 0.11 LogMAR, with LEA reporting better acuity. The difference depended on age, with children aged <4 years exhibiting greater VA differences (0.27 LogMAR) while differences were smaller in children aged ≥4 years (0.09 LogMAR); in an additional adult control group the VA values of LEA and FrACT were even closer with 0.02 LogMAR mean difference. The 95% limits of agreement of test–retest‐variability of VAs in the FrACT were ± 0.29 LogMAR with a bias of 0.017 LogMAR (better acuity for the first test run). Conclusions: The FrACT, as an examiner‐independent tool using international reference Landolt C optotypes, can be reliably used to assess VA in preschool children aged 4 years and older. We confirm that the LEA Symbols Test reports better acuity than tests based on Landolt rings.